Twenty-nine women to 906 men: Continuing gender inequality on the boards of Germany's top companies - Elke Holst; Julia Schimeta (Weekly Report, 2011)
The executive boards1 of Germany's 200 largest companies are still almost all male. In 2010, women occupied only 3.2% of all board seats. This negligible percentage is even lower in the top 100 and DAX30 companies, which are only 2.2% female, despite a voluntary commitment dating back to 2001, in which companies promised to give more women access to senior positions. A similar, although less extreme picture can be seen on the supervisory boards. On average, 10.6% of all supervisory board members in the top 200 companies were women; 30% of all supervisory boards examined in this study were 100% male. Most of the women (70%) were appointed as employee representatives under codetermination legislation. The massive underrepresentation of women on the boards of Germany's top businesses has remained virtually unchanged for years. Since the data show non-binding commitments to be ineffectual, companies will have to set clear targets and monitor them consistently to achieve a significant near-term increase in the proportion of women in senior management.
Keywords: J16; L25; L32; M14; M51; 330; board diversity; women CEOs; gender equality; management